2015
DOI: 10.1021/acs.jafc.5b01682
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-atherosclerotic Dipeptide, Trp-His, Reduces Intestinal Inflammation through the Blockade of L-Type Ca2+ Channels

Abstract: Trp-His, the anti-atherosclerotic dipeptide, exerted an antiproliferative effect on vascular smooth muscle cells by L-type Ca(2+) channel blocker-like effect. The beneficial potential by the blockade of Ca(2+) channels on chronic intestinal inflammation, including inflammatory bowel disease (IBD), is unclear. Trp-His (100 or 250 mg/kg body weight/day) was administered for 14 days to BALB/c mice, and 5% dextran sodium sulfate (DSS) was administered to induce colitis in the last 7 days. Trp-His reduced DSS-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
(79 reference statements)
2
18
0
Order By: Relevance
“…Given the concerns about the side effects, there has been also a substantial increase in public and scientific awareness about natural compounds and their derivatives as safer alternatives for the treatment and management of chronic diseases. A substantial amount of scientific evidence has suggested that food‐derived compounds, both nutrients and non‐nutrients, can modulate chronic inflammatory conditions . Food‐derived compounds are not organ‐ or tissue‐specific and may modulate both pro‐inflammatory and/or anti‐inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Given the concerns about the side effects, there has been also a substantial increase in public and scientific awareness about natural compounds and their derivatives as safer alternatives for the treatment and management of chronic diseases. A substantial amount of scientific evidence has suggested that food‐derived compounds, both nutrients and non‐nutrients, can modulate chronic inflammatory conditions . Food‐derived compounds are not organ‐ or tissue‐specific and may modulate both pro‐inflammatory and/or anti‐inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…There are four possible mechanism pathways for BAPs to attenuate chronic intestinal inflammation: NF- κ B, MAPK, Janus kinase-signal transducer and activator of transcription (JAK-STAT), and peptide transporter 1 (PepT1) ( Figure 2 ) [ 2 , 7 , 10 , 20 , 37 41 ]. Through inhibiting these pathways, BAPs can act the anti-inflammatory function in intestinal cells.…”
Section: Pathways Involved In the Inhibition Of Chronic Intestinalmentioning
confidence: 99%
“…After being stimulated, JNK accumulates in the nucleus and causes the corresponding gene (IL-1 and TNF- α ) expression, resulting in inflammatory response ( Figure 2 ) [ 44 ]. Various food protein-derived BAPs can inhibit inflammation via this MAPK pathway, such as DEDTQAMPFR, DEDTQAMPF [ 18 ], FLV [ 20 ], MLGATSL, MSYSAGF [ 18 ], β -Ala-His [ 35 ], pyroGlu-Leu [ 36 ], DIKTNKPVIF [ 45 ], VPP [ 46 ], WH [ 41 ], γ -EC, and γ -EV [ 47 ].…”
Section: Pathways Involved In the Inhibition Of Chronic Intestinalmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, uptake of small peptides by the oligo/dipeptide transporters (pept1) provides an effective and energy‐saving intracellular source of AA . Recently, several dipeptides have been identified to exert various physiological functions, such as antiatherosclerotic effects (Trp‐His) , antioxidant function (Ala‐Gln and Asn‐Trp) , and anti‐inflammatory (Gln‐Cys and Gln‐Val) . Thus, dipeptides containing Lys are expected to exert positive effects in the application fields of which free Lys or its salts show lower bioavailability.…”
Section: Introductionmentioning
confidence: 99%